Effects and safety of herbal medicines on patients with overactive bladder: A protocol for a systematic view and meta-analysis. Issue 37 (September 2019) - Zhou, Jin; Jiang, Chenglong; Wang, Peng; He, Shen; Qi, Zirong; Shao, Shujun; Tang, Yinshan
Abstract: Background: Overactive bladder (OAB) is a common disease in the urinary system. The morbidity is increasing annually. Herbal medicines have been pervasively used in the therapy of OAB. However, systematic review or meta-analysis has not been found to assess the effects and safety of herbal medicines in curing OAB at present. Hence, the systematic review is conducted to scientifically and methodically evaluate the value of its effectiveness and safety of herbal medicines on OAB. Methods: We will collect all randomized controlled trials (RCTs) to assess the effectiveness and safety of herbal medicines on OAB. The RCTs will be searched from the electronic databases, including 7 English databases, consisting of PubMed, Excerpta Medica Database (EMBASE), MEDLINE, Web of Science, Cochrane Library, SpringerLink, and WHO International Clinical Trials Registry Platform (ICTRP), and 4 Chinese databases, namely Wanfang Chinese database, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), and Chinese Scientific Journal Database (VIP), others valid search strategy will be adopted. All the RCTs will be assessed from the databases establishment to July 2019. We will perform the meta-analysis of RCTs when the dissertation is appropriate. We will conduct an assessment including data synthesis, bias risk, and subgroup analysis by means of Review Manager software (RevMan) V.5.3.5 software while the setting condition is met. Results: This systematic view and meta-analysis will generate a summary based on the current relevant research to calculate the effects and safety of herbal medicines in promoting the therapy of OAB. Furthermore, it will provide a high-quality synthesis for participants who use herbal medicine to cure OAB. Conclusion: The summary of our systematic view will verify whether herbal medicines intervention could be an effective and safety approach in curing OAB.